The impact of international economic sanctions on economic development: Iran is a model (Entrepreneurship Journal for Finance and Business, 2025)
The issue of international sanctions on Iran because of its nuclear program is one of the thorny and complex issues due to the differing positions of the countries of the region on the Iranian nuclear program and on the relations between Iran and the countries of the region, as well as the position of the United States of America, the most influential power in the file of this program.The economic sanctions on Iran prompted the latter to continue its nuclear program and return to the arms race in many different forms and manifestations, but this led to a decline in Iran’s economic capabilities, especially its financial ones, and a restriction on Iranian oil production as it constitutes the main and important resource along with gas in running the wheel of the energy economy, and a decrease in Iranian oil production. Economic growth and oil exports declined despite Iran adopting the so-called resistance economy or war economy based on smuggling. Iran also faces major political and security challenges in light of the risks surrounding it, in addition to increasing interference in its internal affairs due to the increasing number of expatriate workers in its societies. The pretext of labor-exporting countries to provide them with protection and incite political and religious conflicts, not to mention the fear of the outbreak of a direct military confrontation, which portends a humanitarian catastrophe with undesirable consequences. The most prominent results were the impact of international economic sanctions on the gross and real domestic product, economic development, and the high rate of inflation and unemployment, which made The Iranian economy is vulnerable to structural imbalances and the loss of its role in global economic activities.